Measurement of the 239Pu(n,f)/235U(n,f) Cross-Section Ratio with the NIFFTE fission Time Projection Chamber - Snyder, L.; Anastasiou, M.; Bowden, N.S.; Bundgaard, J.; Casperson, R.J.; Cebra, D.A.; Classen, T.; Dongwi, D.H.; Fotiades, N.; Gearhart, J.; Geppert-Kleinrath, V.; Greife, U.; et al. (Nuclear data sheets, 2021)
The 239Pu(n,f)/235U(n,f) cross-section ratio has been measured with the fission Time Projection Chamber (fissionTPC) from 100 keV to 100 MeV. The fissionTPC provides three-dimensional reconstruction of fission-fragment ionization profiles, allowing for a precise quantification of measurement uncertainties. The measurement was performed at the Los Alamos Neutron Science Center which provides a pulsed white source of neutrons. The data are recommended to be used as a cross-section ratio shape. A discussion of the status of the absolute normalization and comparisons to ENDF evaluations and previous measurements is included.